Acute Psychological Distress and Metabolic Findings in a Young Adult with Emotionally Unstable Personality Disorder: A Case Report - V, Hemashree; R, Ranjith Kumar; Sharjun S, Mohamed; M, Abul Yasar; Priya, K. Bharathi (International Journal of Aquatic Research and Environmental Studies, 2026)
We present the case of a 20-year-old female, Ms. S.P.T., with a known diagnosis of Emotionally Unstable  Personality Disorder (EUPD), who was admitted to the inpatient psychiatric unit with acute-on-chronic  psychological distress. Her presentation was precipitated by a complex psychosocial crisis involving a recent  elopement, marriage to a man with a significant family history of substance abuse, and subsequent marital discord,  including alleged abuse. An initial inpatient assessment revealed a patient in significant distress. Routine  laboratory investigations were conducted to rule out organic causes for her presentation and to establish a baseline  for management. The results revealed notable metabolic abnormalities, including Vitamin B12 deficiency (160.6  pg/mL) and Vitamin D insufficiency (23 ng/mL), alongside a lipid profile with elevated LDL cholesterol (147  mg/dL) and low HDL cholesterol (39 mg/dL). Her thyroid function and other routine parameters were within  normal limits. This case highlights the critical importance of comprehensive metabolic screening in young  psychiatric inpatients. It underscores that while the primary presentation is often psychosocial, underlying  physiological abnormalities are common and can significantly impact both physical and mental health outcomes.  The case advocates for integrated care models in psychiatry that address both psychological and biological factors  from the point of admission.